Early adiposity rebound: predictors and outcomes - Alessandra Li Pomi; Giorgia Pepe; Tommaso Aversa; Domenico Corica; Mariella Valenzise; Maria Francesca Messina; Letteria Anna Morabito; Stefano Stagi; Malgorzata Wasniewska (BMC, 2024)
Abstract Adiposity rebound (AR) refers to the second rise of the body mass index (BMI) curve that usually occurs between six and eight years of age. AR timing has a significant impact on patients' health: early AR (EAR), usually before the age of five, is considered to be the earliest indicator of obesity and its related health conditions later in life. Many studies have evaluated factors that can be predictors of EAR, and identified low birth weight and gestational weight gain as novel predictors of EAR, highlighting the role of the intrauterine environment in the kinetics of adiposity. Furthermore, children with breastfeeding longer than 4 months have been found to be less likely to have an EAR, whereas children born to advanced-age mothers, high maternal BMI had a higher risk of having an EAR. Some differences were found in the timing of AR in boys and girls, with girls being more likely to have EAR. The aim of this review is to answer the following three questions: 1) Which are the prenatal and perinatal factors associated with increased risk of EAR? Is gender one of these? 2) Which are the outcomes of EAR in childhood and in adulthood? 3) Which measures can be taken in order to prevent premature AR?